Rumus Slovin : Panacea Masalah Ukuran Sampel ? - Santoso, Agung (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2023)
Slovin’s formula was a popular formula employed to calculate sample size in psychological research in Indonesia. There were not many Indonesian academic publications in Psychology discussing the use of the formula. Most of discussion regarding the use of the formula were conducted in social media platform, which were incomplete or inaccurate at their best. The current article was written to provide a deeper look at the formula and its limitation. One simulation study was conducted to provide empirical basis for evaluating the use of the formula in different contexts. It was concluded that the application of Slovin’s formula was limited to a very specific research context and that employing the formula for calculating sample sizes in different contexts may result in lower precision of parameter estimation.